Metode untuk Mempertahankan Kandungan Nitrit Sarang Burung Walet Selama Penyimpanan - Utomo, Budi ; Widyaratri, Yuni ; Widyanto, Rahma Micho (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Wallet bird nest is a nest that can be consumed by humans, which is made from male swallow's saliva. Male swallow bird makes a nest with its saliva for 35 days. The purpose of this study was to determine the number of TPC (Total Plate Count), nitrite and L * a * b. The material of this study is wallet bird's nest. The method used is Completely Randomized Design (CRD) with 3 treatments and 4 replications P0 = Without treatment, P1 = room temperature, P2 = Freezer no vacuum, P3 = Vacuum freezer. The results showed that the best TPC test results obtained by room temperature treatment were 461.25 ? 39.167 x 104, and the best nitrite test was obtained in vacuum freezer treatment ie 1.42 ? 0.059, and the best L * a * b color test on room temperature treatment 1.50 ? 0.520. Conclusion of the results of this study is the best treatment in this study is the storage of swallow's nests at freezer temperature using vacum packaging seen from the TPC parameters, nitrite and redness level using the L * a * b * color meter instrument.